(untitled) (Global Conference on Medical and Health Sciences, 2026)
Background: Hypertension remains one of the most prevalent cardiovascular disorders worldwide, affecting approximately 1.28 billion adults and representing a leading risk factor for stroke, myocardial infarction, and chronic kidney disease. Despite significant advances in antihypertensive therapy, the pathophysiological mechanisms underlying sustained elevation of arterial blood pressure are not yet fully elucidated. Objective: This study aimed to systematically investigate the alterations in neurohormonal, vascular, and renal regulatory mechanisms contributing to the development and maintenance of hypertension. Methods: A comprehensive review and meta-analysis of peer-reviewed studies published between 2010 and 2024 was conducted. Data were extracted from randomized controlled trials, observational cohorts, and experimental animal models. Key parameters analyzed included renin-angiotensin-aldosterone system (RAAS) activity, sympathetic nervous system (SNS) tone, endothelial function, arterial stiffness, and baroreceptor sensitivity. Results: Findings demonstrated that hypertensive patients exhibit a significant upregulation of RAAS components, with plasma renin activity and angiotensin II concentrations elevated by 34% and 41%, respectively, compared to normotensive controls (p<0.001).